Drug ampoules in rectum: Lucky co-incidental finding in emergency department of eastern Nepal - Giri, Saroj; Gupta, R; Bhandari, R; Chaudhuri, S (Health Renaissance, 2017)
Background: Rectal foreign body is uncommon in emergency usually presenting after failure to remove the object manually or with other complications. Case: Twenty two years male in emergency department presented with rectal leeding following a manual attempt to remove drug ampoules from rectum. Conclusion: In an unexplained rectal bleed, foreign bodies could be a pitfall. Health Renaissance 2015;13(3): 185-187